Dietary Intake and Supplement Use in Competitive Women Bodybuilders - John E. Haubenstricker; Jerry W. Lee; Gina Segovia-Siapco; Ernesto Medina (MDPI AG, 2023)
(1) Background: Women bodybuilders use extreme diets, dietary supplementation, and training regimes to sculpt their physiques. Women's participation in bodybuilding competitions has increased since the 1980s. Currently, studies on their dietary intake and supplement use are limited. Their dietary intake may be of poor quality and low in several micronutrients, while supplement use appears to be omnipresent. Thus, the aim of this study was to examine and compare the dietary intake, supplement use, and diet quality of in-season and off-season women bodybuilders. (2) Methods: In a cross-sectional design, we compared dietary intake, supplement use, and diet quality between seasons in women bodybuilders (n = 227). An online questionnaire was developed, validated, and administered to assess all non-dietary and supplement variables. The Automated Self-Administered 24 h Dietary Assessment Tool was used to collect four 24 h dietary recalls. The Healthy Eating Index-2015 (HEI-2015) was used to calculate diet quality. The analysis of covariance and Welch's t-tests were used to assess the differences between in-season and off-season women bodybuilders' dietary intake, supplement, and HEI-2015 variables. (3) Results: In-season competitors reported consuming significantly less energy, carbohydrates, and fat but more protein than off-season competitors. All competitors consumed excess protein, while in-season competitors consumed excess fat and off-season competitors consumed less energy than the physique athlete nutrition recommendations. All competitors' micronutrient intakes were above the Dietary Reference Intakes. Supplements were used by all competitors, and the mean number used was similar between seasons. The HEI-2015 scores were not significantly different between seasons yet were below the US Dietary Guidelines for Americans. (4) Conclusion: Women bodybuilders would benefit from health education to achieve physique athlete nutrition recommendations, improve diet quality, and safe/efficacious supplement use to reach physique goals and improve overall health.